Novel cross-linked partially fluorinated and non-fluorinated polyaromatic PBI-containing blend membranes for SO2 electrolysis. (27th July 2016) - Peach, Retha; Krieg, Henning M.; Krüger, Andries J.; Rossouw, Jacobus J.C.; Bessarabov, Dmitri; Kerres, Jochen
Abstract: Various partially fluorinated and non-fluorinated polyaromatic and PBI blend components were covalent-ionically cross-linked to obtain proton exchange membranes that can be applied in an SO2 electrolyser. During SO2 electrolysis, SO2 and H2 O are converted to H2 and H2 SO4, which implies that the membranes to be used for this process should have both a high proton conductivity and H2 SO4 stability. The acid stability of the blend membranes were evaluated in an 80 wt% H2 SO4 environment for 120 h at 80 and 95 °C respectively. From the characterization results obtained by monitoring weight and thickness change, IEC, SEM-EDX and TGA signal's before and after treatment, it was determined that the novel cross-linked blend membranes, containing only partially fluorinated polymer components, showed exceptional stability. The cross-linked partially fluorinated polyaromatic PBI blended membrane (SFS001-F6 PBI-BrPAE) and Nafion ® 115 were selected for electrochemical evaluation by obtaining polarization curves at 80 and 95 °C. The SFS001-F6 PBI-BrPAE performed the best at operation temperature of 95 °C reaching a current density of 0.63 A cm −2 in comparison to the 0.42 A cm −2 obtained for Nafion ® 115 at 1.0 V. Durability of the membranes within the electrolyser were measured by means of voltage stepping and subsequent characterization using SEM-EDX, TEM and TGA which confirmed the minimal degradation observed for the 250 cycles completed. Highlights: Partially fluorinated polymer components showed exceptional chemical stability after H2 SO4 treatment. Improved performance noted for fluorinated polyaromatic PBI-containing blend membrane in SO2 electrolyzer at 95 °C. Durability of blend membrane and Nafion ® evaluated with voltage stepping. Good long term stability observed for blend membrane at 95 °C.